Development of a CanSat - Zhang, Yunjie. (2013)
In this Final year project, a CanSat system that uses in-house microcontroller processor board is designed and implemented. The system is capable to collect and transmit data from the CanSat to the ground station. Such a training kit can be provided to the secondary school students as it gives an opportunity to be involved in a complex CanSat project from conceptual design through software development, hardware integration and testing of the system.